(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Title Snapshot of MRI neural axis abnormalities seen in consecutive cohort of pediatric and young adult patients undergoing spinal deformity correction in tertiary care hospital setting in Pakistan AshfaqAhmed , Abdullah Shah , Majid Zaheer,Ammar Dogar , RizwanAkram , Amer Aziz Introduction The pre-operative use of MRI to identify occult intraspinal anomalies before surgical correction of paediatric spinal deformity contributes widely accepted best practice recommendations. However due to economic and resource constraints these recommendations are not universally implemented in many health-care settings. Study was conducted to document the frequency and types of encephalomyelonic Axis Anomalies found in a consecutive cohort of paediatric and young adult patients undergoing spinal deformity surgery with the aim of consolidating the case for pre-operative MRI imaging of all surgical patients. Methods Departmental prospective database used to identify consecutive paediatric and young adult patients undergoing scoliosis correction between January 2015 and December 2018 at a tertiary spine referral center in Pakistan. Data collected on clinical and MRI findings. Clinical data included age, sex, scoliosis type (idiopathic, congenital, neuromuscular & syndromic) and presence of abnormal neurological findings. MRI data included presence and type of neural axis abnormalities (NAA). Results 87 patients were included having the diagnosis of idiopathic and congenital scoliosis, and from these patients, 33.3% (n =29) were male, and the majority were female patients as 66.7% (n=58) diagnosed with a different type of scoliosis (Idiopathic or congenital) with an average age of 13.7±3.87 ranged from (4-27) years. Idiopathic and congenital scoliosis were found as 56 ( 64.4% ) and 31 (35.6 % ) respectively. Considering divergent anomlies , Diastomyelia was documented in 4 (04.59 %) .likewise ,Tethered Cord in 2 ( 2.29 % ) patients , 10 ( 11.49 % ) of patients had Syringomyelia and Chiari Malformations was noticed in 2 ( 2.29 % ) patients. Lipoma and diplomyelia was not screened in single patient. However, 2 (2.29% ) was having dural fault, conus 9 ( 10.34 % ) and 1 (1.15% ) foramen magnum compression. When rare anomalies were viewed ,Hydromyelia was detected in 3 (3.44 % ), tonsillar ectopia in 2 (2.29% ) and OS Odontoideum in 1(1.14% ).Moreover,only 5 (5.74% ) of patients having neurology involved while other were having intact neurology. Conclusion ;Patients with scoliosis having discrete anamolies that can be missed on clinical examination and X-rays. Pre operative Magnetic Resonance Imaging has vital role to identify these peculiar abnormalities in these patients before considering any surgical intervention.